Conservative leaf economic traits correlate with fast growth of genotypes of a foundation riparian species near the thermal maximum extent of its geographic range. (15th February 2013) - Grady, Kevin C.; Laughlin, Daniel C.; Ferrier, Sharon M.; Kolb, Thomas E.; Hart, Stephen C.; Allan, Gerard J.; Whitham, Thomas G.; Knapp, Alan
Summary Plant functional traits involved in carbon and water acquisition are likely to be adaptive across the range of a species if the availability of these resources varies across this range and are limiting to growth or fitness. At the interspecific level, leaf economic traits associated with rapid resource capture are correlated with fast growth rates. However, relationships between leaf traits and growth are poorly understood at the intraspecific level. We examined two hypotheses: (i) leaf traits vary genotypically among Populus fremontii populations from different thermal environments; and (ii) leaf traits are related to growth rate of these P. fremontii populations. We used a common garden at the warm edge of P. fremontii distribution that included individuals transplanted from 11 provenances. Provenances varied in mean annual maximum temperature by 5·9 °C, reflecting a range of expected increases in temperature over the next 80 years. Conservative leaf traits (e.g. low specific leaf area, N content, stomatal conductance, net photosynthetic rate and high leaf water‐use efficiency) were positively related to growth rates of genotypes and populations, a pattern opposite of that widely reported among species in other studies. Provenance temperature explained 75% of the variation in multivariate leaf traits with the warmest provenances having the most conservative traits and highest growth rates. Clinal genetic variation suggests that P. fremontii may be adapted to thermal environments. Leaf area‐to‐sapwood area ratio was positively associated with growth rate, while leaf area‐based net photosynthetic rate was negatively associated with growth rate; these results suggest that hydraulic architecture was more important than leaf‐level photosynthetic rate in determining growth rate. Synthesis. Our results suggest that conservative leaf traits promote rapid growth of P. fremontii genotypes in extremely hot environments. Thus, relationships between leaf economic traits among species do not necessarily apply to the range of variation among genotypes within species. The generality of this pattern should be examined for other species that will be exposed to climate warming. Moreover, our research shows that common garden provenance trials are useful for identifying genotypes best suited to a predicted warmer climate and for improving understanding of the physiological basis for adaptation to warm environments.